Track Record of Islamic Education at Al Fatih Islamic Private Elementary School, Deli Serdang Regency (Historical Study of Islamic Education) - Muhammad Sapii Harahap; Ahmad Zaky; Suhendri Suhendri; Suswanto Suswanto; Fatkhur Rohman; Romat Efendi Sipahutar (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine the development of the Al-Fatih Islamic Elementary School and find out the curriculum used. In this research the author uses historical methods or historical methods. The historical method consists of data collection, source criticism, interpretation and finally historiography. The research approaches used in this research are the geographical approach, sociological approach, educational approach and historical education. The results of this research are 1) Al-Fatih Islamic Elementary School or abbreviated as SD I Al-Fatih was founded in 2014 and is located at Jln. Medan-Tanjung Morawa Gg. Darmo KM. 13.5 Hamlet VII Bangun Sari Village. From the first year to the fourth year, namely 2014-2017, the principal was Ustad Indra Rustam, M.Ag. Then from 2018 until now, the principal was Ustad Ahmad Solihin, S.HI. and received accreditation in 2019 with accreditation B. Currently this school has 276 students. 2) the curriculum used at this Islamic Elementary School is Curriculum 13 and focuses on the Tahfid program, which is mandatory in every class. The number of subjects is 16 lessons, namely: a) Tahfidz, b) Physical Education, Sports and Health (PJOK), c) Arabic, d) Hadith, e) Aqidah Akhlak, f) Indonesian, g) Mathematics, h) Fiqh , i) Qur'an Hadith, j) Pancasila and Citizenship Education (PPKn), k) Arts and Culture, l) History of Islamic Culture (SKI), m) Natural and Social Sciences (IPAS), n) English, o) Social Sciences (IPS), and p) Social Sciences (IPA).